[Rezension von: Jipp, Joshua W., Pauline theology as a way of life : a vision of human flourishing in Christ] - Boyles, John H. (Scottish journal of theology, 2025)
Joshua W. Jipp, Pauline Theology as a Way of Life: A Vison of Human Flourishing in Christ (Grand Rapids, MI: Baker Academic, 2023), pp. x + 278. $ 37.99 - Volume 78 Issue 1